Development of an Interactive Ebook to Improve Cultural Literacy and Citizenship in Class VIII Junior High School Students - Titik Haryati; Suciptaningsih, Oktaviani Adhi; Radeni Sukma Indra Dewi; Novianto Adhi Sucipta (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Cultural and civic literacy is one of the important literacies for junior high school students to have. The aim of this research is to develop an interactive ebook that can increase cultural and civic literacy in class VIII students. The research method uses the Richey and Klein model, namely Research, Design, Production and Evaluation. The participants in this research consisted of seven students and one class VIII teacher at CLC SMPT Lumadan Beaufort, Sabah, Malaysia. The data analysis technique uses quantitative descriptive analysis techniques. The research results show that based on the results of the media validator and ebook material validator it is very valid to be used as a learning medium. Based on the results of the pretest and posttest, there was an increase in students' cultural and civic literacy results. This proves that the interactive ebook created is effective and efficient. Effective because it can increase cultural literacy and citizenship in class VIII students significantly and efficiently because it does not require a long time in the improvement process, namely within one month after using the product in classroom learning.